Comparative Utilization of Dead and Live Fungal Biomass for the Removal of Heavy Metal: A Concise Review - Abate Ayele; Setegn Haile; Digafe Alemu; M. Kamaraj (The Scientific World Journal)
Human and industrial activities produce and discharge wastes containing heavy metals into the water resources making them polluted, threatening human health and the ecosystem. Biosorption, the process of passive cation binding by dead or living biomass, represents a potentially cost-effective way of eliminating toxic heavy metals from industrial wastewater. The abilities of microorganisms to remove metal ions in solution have been extensively studied; in particular, live and dead fungi have been recognized as a promising class of low-cost adsorbents for the removal of heavy metal ions. The biosorption behavior of fungal biomass is getting attention due to its several advantages; hence, it needs to be explored further to take its maximum advantage on wastewater treatment. This review discusses the live and dead fungi characteristics of sorption, factors influencing heavy metal removal, and the biosorption capacities for heavy metal ions removal and also discusses the biosorption mechanisms.